English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

i need help

2007-04-05 08:38:48 · 8 answers · asked by lucy c 1 in Science & Mathematics Mathematics

8 answers

-6u + 7 = -29
-6u + 7 - 7 = -29 - 7
-6u = -36
-6u / -6 = -36 / -6
u = 6

2007-04-05 08:46:04 · answer #1 · answered by Mathematica 7 · 0 0

U=6

2007-04-05 08:42:31 · answer #2 · answered by agkwatson@sbcglobal.net 3 · 0 0

you want to solve for u, what you would do is to put all the integers on the other side of the equation.
-6u + 7 = -29 --> subtract 7 from both sides so that -6u will be the only one on the left.

-6u = -29 - 7 ---> combine like terms and divide both sides by -6 to get u.

-6u = -36
u = 6

2007-04-05 12:45:45 · answer #3 · answered by jeffdeg 2 · 0 0

u = 6

2007-04-05 08:42:58 · answer #4 · answered by dsl67 4 · 0 0

u=6

-29-7 = -36

so

-6u=-36

u=6

2007-04-05 08:42:41 · answer #5 · answered by Anonymous · 0 0

-6u+7=-29
-6u=-36
u=6

2007-04-05 08:42:44 · answer #6 · answered by Minioger 2 · 0 0

The idea is to have the u by itself. You remove whatever is farther. So, you subtract seven from each side. Whatever you do to one side you do to another. The seven on the right side is zero. Then it is negative twenty-nine plus negative seven. That will be negative thirty-six. You divide negative six to both sides. You have to do the opposite so,it will be canceled. That will give you u equals six because a negative divided by a negative is a positive. =6

2007-04-05 08:55:52 · answer #7 · answered by Anonymous · 0 0

-6u=-36
-6u/-6=-36/-6
u=6

2007-04-05 08:43:59 · answer #8 · answered by Dave aka Spider Monkey 7 · 0 0

fedest.com, questions and answers